Mortality risk of surgically managing orthopaedic trauma during the COVID-19 pandemic. (2021) - Balakumar, B.; Nandra, R. S.; Woffenden, H.; Atkin, B.; Mahmood, A.; Cooper, G.; Cooper, J.; Hindle, P.
No abstract available